(untitled) (Web of Teachers: Inderscience Research, 2026)
This study investigates the utilization of authentic materials within the framework of Communicative Language Teaching (CLT) for middle school English classes (Grades 5 to 9, CEFR levels A2 to B1). Such materials include brief videos, podcasts, public announcements, websites, infographics, menus, reviews, and social media posts. The focus centers on a prevalent challenge: students often acquire vocabulary and grammatical structures yet encounter difficulties in comprehending natural language or engaging in authentic conversations outside the classroom environment. By providing opportunities for students to practice real-life language features—such as speech pace, reduced forms, set phrases, social norms, and cultural nuances—the employment of authentic materials proves advantageous. To facilitate the selection and implementation of authentic materials without the necessity of rewriting them into simplified textbook texts, this paper proposes a practical, instructor-oriented framework. The framework encompasses: (1) establishing a clear communicative objective (e.g., information exchange, decision-making, persuasion, or clarification); (2) evaluating linguistic and cultural accessibility, considering factors such as length, speech rate, lexical density, and requisite background knowledge; (3) offering targeted scaffolding through visual aids, key lexical items, sentence starters, and interactional strategies; and (4) designing tasks aligned with the pre–while–post structure. The while-tasks concentrate on understanding the overall meaning and salient details via guided comprehension, whereas the post-tasks involve negotiate meaning and completing outcome-based activities such as role-plays, problem-solving tasks, or collaborative projects. Pre-tasks serve to activate topic familiarity and prepare necessary language.